(untitled) (Agroindustrial Science, 2022)
The objective of this study was to evaluate the sensory attributes and the preference of six canned rainbow trout (Oncorhynchus mykiss) with the addition of government liquid based on yellow chili (Capsicum baccatum) – aguaymanto (Physalis peruviana L.) and hot pepper (Capsicum pubescens) – tree tomato (Cyphomandra betacea) sauces through the preference mapping technique (external and internal mapping). The canned rainbow trout were made with the addition of the governing liquid (corresponding to 4% of the formulation) of 3 types of sauces based on yellow chili - aguaymanto in the proportions of 3/1 (AA-3/1), 2/2 (AA-2/2) and 1/3 (AA-1/3) and 3 types of sauces based on hot pepper – tree tomato 3/1 (RT-3/1), 2/2 (RT-2 /2) and 1/3 (RT-1/3). The evaluation of the sensory attributes was carried out by 10 trained descriptive panelists and the preference by 50 regular consumers of canned and trout meat. The preference mapping indicated that the canned with yellow chili - aguaymanto 3/1 (AA-3/1) presented a greater preference of consumers being greater than 80%, it was also represented in a greater amount by three clusters (2, 1 and 3), this canned was characterized by being more spicy, low sensory acidity, less texture and less salty taste.